Manipulation of the aquatic physical environment and its relationship with ectoparasitic infection in dumbo catfish (Clarias sp) - Suratno Suratno; Suryono Suryono; Muhammad Naswir (Depik, 2023)
Fish disease is an obstacle in the cultivation of Dumbo catfish (Clarias sp.) which can result in fish death. The need for information on how to prevent and treat fish diseases is very necessary. This study aims to determine the effect of aeration duration on water quality, ectoparasite intensity, prevalence, dominance, survival and condition factors, then correlate water quality with ectoparasite intensity. This study used a Complete Randomized Design (CRD) with five treatments and four replications. Treatment includes aeration 0 hours/day, 6 hours/day, 12 hours/day, 18 hours/day and 24 hours/day. Data analysis using ANOVA of a certain level of significance. If there is a noticeable difference from each treatment, proceed to the DUNCAN test. Test the correlation of water quality with ectoparasite intensity. The result of this study is that long aeration can increase oxygen solubility, acidity but reduce ammonia and nitrite. The correlation value of oxygen solubility in ectoparasite intensity is 0.828, acidity (pH) is 0.849, ammonia is -0.888, nitrite is -0.592. The prevalence value of P0 and P1 is 0%, P2 is 89%, P3 and P4 is 100%. The intensity of ectoparasites in Dumbo catfish (Clarias sp.), at P0 is 2, P1 is 13, P2 is 75, while at P3 and P4 is 100. The dominance of ectoparasites that infect is Trichodina sp. by 71.7-100% and Dactylogyrus sp. by 0-28.4%. The survival rate of fish at P0 was highest with a value of 89%, P1 at 84%, P2 at 71%, P3 and P4 rates at 0%. The value of the condition factor then P0 and P1 have a value of 1, P2, P3 and P4 have a condition factor value of 1. It is concluded that the longer aeration is given, the solubility of oxygen increases which results in an increase in the intensity and prevalence of ectoparasite infections, the pH of the water becomes neutral and decreases the content of ammonia and nitrite. There is a moderate to very strong correlation between water quality and ectoparasite intensity. There is an increase in the prevalence of infection, ectoparasite intensity and fish mortality so that it can reduce the survival and condition factors of Dumbo catfish (Clarias sp.).Keywords:AerationInfectionEctoparasitesClarias sp